Conflictul materno-fetal, ca o extremitate a dimensiunii protecției copilului [Articol] - Balcan, Silvia (CEP USM, 2022)
Obviously, the child is protected by legal norms at national and international level from the birth moment, and this article aims to present the request for the protection of the child at a stage prior to the establishment of extrauterine life, starting also from the provisions of some international instruments. In the scientific work, we will assess the need for rationale towards the balance between the sexual, reproductive and intrauterine life rights and those of persons’ intrauterine life. The formulated conclusions will outline the need to review the national legislation, including the involvement of specialists from different fields, so that through research and studies focused on the good practices implemented in the experience of other states, recourse may be had to the harmonization of national legislation in the field of right protection to life of unborn children.
Keywords: unborn child; right to life; fetus; abortion